Hall itme motorlarının boyutlarına göre performansının incelenmesi - Sönmez, Okan (İstanbul Kültür Üniversitesi / Fen Bilimleri Enstitüsü / Fizik Anabilim Dalı, 2014)
Bu çalışmada Hall itme motorunun pülüm geometrisini geliştirmek için kullanılan, Soğan Modeli kullanılarak, Hall itme motorunun çeşitli performans parametreleri ve voltaj verimi incelenmiştir. Modelden elde edilen verilere göre, Hall itme motorunun pülmü boyunca oluşan itme kuvveti işlemi sırasında, belli bir aralıkta plazma parçacıklarının izlediği yolun eğri bir yol olduğu, daha sonra ise eğriliğin sıfıra çok çok yaklaşarak, bu parçacıkların paralel bir yol izlediği aşikar olarak ortaya konmakta, bu iniş ve çıkışların ise, oradaki çarpışmalardan kaynakladığı anlaşılmaktadır. Bu sonuç itibari ile de, model verileri ile literatürden alınan deney verilirinin örtüştüğü yine bu çalışmada ortaya konmaktadır.
We studied the variations of performance parameters and voltage efficiency with the size of Hall thruster by using onion model developed for the geometry of the Hall thruster plume and experimental result corresponding to three mini-Hall thrusters. When the result from the model were compared with the experimental studies from literature, it was found that performance parameters and voltage efficiency of a mini- Hall thruster exhibit fluctions on the hump of plume and remain constant along the tail of the plume and the size of hump depends on radial size of the thruster as expected. Also, the curvature of particle trajectories on the plume fluctuated in the hump and appoaches to zero along the tail. To conclusion, in the hump region the collisions between the exhausted particles could lead to the higher curvature of radius. Along the tail the particles from beams, without making collisions. Numerical values of performance parameters in the tail are the same with the experimental values for a certain particle densities.
Keywords: fizik; fizik mühendisliği; physics; physics engineering